Pengaruh DER, TATO dan CR Terhadap Profitabilitas Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Hizkia Putri Butar Butar; Iman Indrafana (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the effect of debt to equity ratio, total asset turnover and current ratio on profitability with company size as a moderating variable in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2019-2023. This study uses a population of 130 consumer non-cyclicals companies. A sample of 37 companies was selected using purposive sampling method, with a research period of 5 years so that 185 observation data were obtained. The data analysis technique used in this research is multiple linear regression and MRA using the SPSS 26 tool. The results of this study indicate that the debt to equity ratio and total asset turnover have a significant effect on profitability, while the current ratio has no effect on profitability. Company size is unable to moderate the effect of debt to equity, total asset turnover and current ratio on profitability in consumer non-cyclicals companies listed on the IDX in 2019-2023.